Estrategia de marketing para la promoción y fomento del uso de los pasos elevados peatonales en la vía perimetral de la ciudad de Guayaquil año 2014 - Peña Álvarez, Erika Yuliana (2015)
Driver education is one of the areas which will reduce the population that has broad implications for the traffic accident, which is why the goal of designing a social marketing strategy of road culture, to promote and encourage raised the massive use of pedestrian overpasses, to help reduce the risk of traffic accidents of pedestrians in the Perimeter Road city of Guayaquil, for this purpose, a survey was conducted to pedestrians through a descriptive, deductive and quantitative results, which demonstrate that only 24% of the population used the overpass, 79% hold low levels of education, from the other side of the perimeter road frequently every day, 72% have not heard any information, and dissemination of road safety education, let alone in relation to the incentive for the use of high pedestrian crossings in the area of the perimeter road, one of the most dangerous in urban traffic, which is why the application was proposed Social Marketing strategy with flow multistage road for the promotion and dissemination to promote the strengthening of knowledge of the importance of using overpasses, together with education and awareness plan for pedestrians in road safety, through advertising spread in mass media and scheduled events with the participation of the Transit Commission of Ecuador, public institutions of educational, social and cultural sector, the private sector, NGOs, proposing permanent evaluation Pedestrian leveraging technology Eagle Eye to corroborate that pedestrians respect the Traffic Act, under the third objective of good living…..